Kajian Interferensi Koefisien Hambatan pada Lambung Katamaran melalui Komputasi ’Slender Body Method - Jamaluddin, Andi; Utama, I Ketut Aria Pria; Hamdani, M.Arief (Department of Naval Architecture - Diponegoro University, 2010)
The past decade has witnessed a rapid growth of interest in the development of fast catamaran for various applications. The paper describes the study of interference resistance components on demihull separation. Catamarans or twin-hull vessels may be formed either by connecting two symmetrical demihulls or by splitting a mono hull into two halves to form two asymmetric demihulls. The slender body method in HullSpeed- Maxsurf Program was used for predicting the resistance components. The method assumes that the ship’s beam is small compared to its length. Effect of resistance interference components on catamaran hull separations are explained and discussed with some work from other published data, which shows good agreement.